The Influence of Inhibitors of Plasmin and Plasminogen Activation on the Streptokinase-Induced Fibrinolytic State - Spöttl, F; Holzknecht, F (Thrombosis and Haemostasis, 1970)
The influence of the inhibitors of plasminogen activation by streptokinase, urokinase and tissue activator and of the two antiplasmins i.e. α1 antitrypsin and α2-macroglobulin, upon the formation and clearance of streptokinase-activator in vivo was investigated in 22 subjects. No influence of the above mentioned inhibitors on the formation of the streptokinase-activator could be found, whereas the clearance of the activator seems to be a function of the α2-macroglobulin level before streptokinase administration. The clearance rate of the streptokinase-activator differed significantly from the clearance rate of 131I labelled streptokinase caused by antigen-antibody complex formation [Fletcher et al. (10)], and was similar to the clearance rate of the histamine or nicotinic acid induced plasminogen activator. The possibility of a common clearing mechanism of fibrinolytic activators is discussed.The existence of 3 different inhibitors activities on plasminogen activation as tested in vitro i. e. inhibitor of streptokinase, urokinase and tissue activator, was demonstrated. These inhibitory activities are probably not the properties of 3 different serum proteins but rather the result of the action of α1antitrypsin and α2-macroglobulin. The degree of inhibition, however, of each of the 2 proteins on each of the 3 plasminogen activators (streptokinase, urokinase and tissue activator) seems to be different. This difference may be caused by a different inhibitory effect of α1 antitrypsin or α2-macroglobulin on each of the plasminogen activators.The plasmin formed after the streptokinase infusion is rapidly bound by the α2macroglobulin and this plasmin-antiplasmin complex is immediately removed from the blood, causing a decrease of the α2-macroglobulin level. This decrease of α2-macroglobulin is correlated with the initial level of α2-macroglobulin. This finding demonstrates the concentration depending formation of the plasmin-antiplasmin complex also in vivo.